CULTURAL IDENTITY AS TOURISM BRANDING FOR EAST JAVA PROVINCE IN INSTAGRAM CONTENT @DISBUDPARJATIMPROV - Sulistyo Budi Utomo; Soni Suharmono; Garcia Krisnando Nathanael; Tono Mahmudin; Tugas Tri Wahyono (ITB AAS Indonesia Surakarta, 2024)
This research aims to (1) find out how the cultural identity displayed by the East Java culture and tourism department as East Java tourism branding in the Instagram content @disbudparjatimprov; and (2) determine the effectiveness of the East Java culture and tourism agency's tourism branding by highlighting East Java's cultural identity. This research is qualitative-descriptive research. The primary data source used in this research is East Java Disbudpar Instagram content. The data analysis technique in this research uses the Miles and Huberman perspective in the form of data presentation, data reduction, and drawing conclusions. The results of this research show that (1) Cultural identity as East Java tourism branding in Instagram @disbudparjatimprov content contains dimensions of entertainment, interaction, trends and customization; and (2) East Java Disbudpar takes advantage of tourism promotion opportunities through social media along with the advantages of the Instagram platform which is easy, global and interactive, being an effective and cheap way compared to promoting tourism through other media.